Metode Accumulative Difference Images untuk Mendeteksi Berhentinya Putaran Kincir Air - Adri Priadana; Aris Wahyu Murdiyanto; Aris Wahyu Murdiyanto (JISKA (Jurnal Informatika Sunan Kalijaga), 2021)
Vannamei shrimp is one of Indonesia's fishery commodities with great potential to be developed. One of the essential things in shrimp farming is a source of dissolved oxygen (DO) or a sufficient amount of oxygen content, which can be maintained by placing a waterwheel driven by a generator set engine called a generator. To keep the waterwheel running, the cultivators must continue to monitor it in real-time. Based on these problems, we need a method that can be used to detect the cessation of waterwheel rotation in shrimp ponds that focuses on the rotation of the waterwheel. This study aims to analyze the performance of the Accumulative Difference Images (ADI) method to detect the stopped waterwheel-spinning. This method was chosen because compared with the method that only compares the differences between two frames in each process, the ADI method is considered to reduce the error-rate. After all, it is taken from the results of the value of several frames' accumulated movement. The ADI method's application to detect the stopped waterwheel-spinning gives an accuracy of 95.68%. It shows that the ADI method can be applied to detect waterwheels' stop in shrimp ponds with a very good accuracy value.